MODELING OF SPATIAL-TEMPORAL VARIATIONS OF DYNAMIC AND THERMAL PROCESS PARAMETERS IN GEOSPACE OVER UKRAINE DURING THE MINIMUM OF 24-TH CYCLE OF SOLAR ACTIVITY (2009, 2019) - Kolodyazhny, V. V.; Lyashenko, M.V.; Emelyanov, L.Ya; Dzyubanov, D.A. (Kosmìčna nauka ì tehnologìâ, 2023)
We have performed the modelling of spatiotemporal variations of parameters of dynamic and thermal processes in ionospheric plasma at the phases of the minimum of the 24-th cycle of solar activity according to the Kharkiv radar of incoherent scattering. The diurnal dependences of parameters of the processes in the ionospheric plasma at altitudes from 210 to 450 km are constructed for typical geophysical periods (vernal and autumn equinoxes, summer and winter solstices). In the paper, the analysis of spatial and temporal variations of parameters of dynamic and thermal processes in the ionosphere is presented. We determined the value of the plasma transfer velocity due to ambipolar diffusion, the density of the full plasma flux, and the flux of charged particles due to ambipolar diffusion, the value of the energy supplied to the electron gas, the density of the heat flux transferred by electrons from the plasmasphere to the ionosphere, as well as the velocity of the equivalent neutral wind, and the meridional component of the neutral wind velocity. We found that weak variations in space weather do not lead to significant changes in spatiotemporal variations of the parameters of dynamic and thermal processes in the ionosphere for most of the studied periods. Quantitative and qualitative characteristics of most of these parameters and their diurnal variations were typical for the considered seasons. On the contrary, the velocity of the equivalent neutral wind changed significantly (up to 2—2.5 times) even with a weak increase in geomagnetic activity. The reasons for such changes may be the strengthening of horizontal thermospheric winds and the penetration of zonal magnetospheric electric fields into midlatitudes during the equinoxes. The obtained results of calculations can be used in basic studies of solar-terrestrial relations and geospace, for the solution of applied problems related to the ability to predict the state of space weather, as well as for further development of the regional ionosphere model CERIM IION. The object of research: physical processes in the ionospheric plasma. The subject of research: spatiotemporal dependences of the main parameters of ionospheric plasma, which were obtained using incoherent scattering radar. Research methods — terrestrial radiophysical method of incoherent scatter of radio waves, statistical analysis of observation results, semi-empirical modelling of parameters of dynamic and thermal processes.